Mozart in Paris: 'Les Mystères d'Isis'. An opera in four acts (De Musica, 2023)
Les mystères d’Isis is one of the most controversial works in the history of Western music. Despite being very famous in the nineteenth-century French and especially Parisian period, today it is almost forgotten. In the Italian musicological context, the opera is poorly studied and there is a lack of literature on the subject. Born in 1801 from the adaptation of the Mozartian The magic flute, it has been created by the collaboration between Ludwig Wenzel Lachnith (1746-1820), who arranged the music, and Étienne Morel de Chédeville (1751-1814). The adaptation of works, especially foreign ones, is a practice in nineteenth-century theater, but this time something more happens. While the libretto is totally rewritten, the music is partly modified from the original work and arias from Don Giovanni and Clemenza di Tito are added. The result is a work that aroused the public’s favor with regard to music, scenography and ballets, but the libretto was extremely criticized. Despite the textual criticism, it had over 120 performances in Paris allowing the vast public to make Mozart famous as an opera composer. Indeed, Mozart had been to Paris in 1778 without reaching great visibility. Although it gave rise to the dissemination and appreciation of Mozart, it had a critical point: the original version of The Magic Flute did not appear in Paris before 1865 and in French. This meant on the one hand the success of Mozart as composer but on the other it witnessed a difficult permeation of the original work in France for a long period after the composer’s death.
Keywords: Mozart; The Magic Flute; French opera; Masonry